Effect of Molasses and Dried Orange Pulp as Sheep Dietary Supplementation on Physico-Chemical, Microbiological and Fatty Acid Profile of Comisana Ewe's Milk and Cheese - Liotta, Luigi; Randazzo, Cinzia L.; Russo, Nunziatina; Zumbo, Alessandro; Di Rosa, Ambra Rita; Caggia, Cinzia; Chiofalo, Vincenzo (Frontiers in Nutrition, 2019)
The use of agro-industrial by-products for ruminant feed represents both an economical and environmental convenient way for reducing waste discharge and waste management costs for food industries. Large amounts of waste from citrus processing industries are available in Sicily, Italy. In the present study, the effect of dried citrus pulp as sheep dietary supplementation was evaluated on physico-chemical, microbiological and fatty acid composition of resulting milk and cheese. Pelleted feed integrated with molasses and blond orange pulp, replacing cane molasses, beet pulp and part of the maize and sunflower in ration, were administrated to ewes as an experimental treatment The experiment involved sixty Comisana breed sheep divided into two groups and two feeding trials (experimental and control). Ewe's milk and cheese samples were collected from January to April and analyzed for physico-chemical, microbiological and fatty acid profile composition. Results suggested that both the experimental milk and cheese were different from the controls. In particular, an increase of experimental milk yield and fat content were registered whilst the cheese samples exhibited a significant decrease of pH values and an increase in fat and protein contents. In addition, an increase of conjugated linoleic acids as well as of the oxidative stability were observed indicating the beneficial effect of dietary supplementation. Furthermore, among the main microbial groups, the experimental and control samples, no differences were detected. However, with the exception of streptococci, which was found higher in experimental cheeses, and staphylococci, which was significantly reduced by experimental feed. Moreover, the application of culture-independent methods highlighted the dominance of Lactobacillus rhamnosus/casei group in the experimental cheese, suggesting a driving role of the dietary supplementation in the cheese microbiota composition. The present study demonstrated that the inclusion of citrus by-products in the diet of small dairy ruminants is a promising feeding, which could positively affect milk composition and cheese manufacture.